Child Psychomotricity: Development, Assessment, and Intervention - Ana Rita Matias; Gabriela Almeida; Guida Veiga; José Marmeleira (MDPI AG, 2023)
Psychomotricity addresses the interactions between psychic functions, motor (and biological) functions, and motor behavior (gestures, posture, attitude, physical activity, and motor skills) [...]